THE QURAN ON PATRIARCHY: A Study of the Concept of Qiwamah in Surah Al-Nisa’ (4): 34 - Fina Lailatul Masruroh, Fina Lailatul Masruroh; Nurilhilmah, Nurilhilmah; Faisal Rojihisawal, Faisal Rojihisawal; Mutamimah, Mutamimah; Ahmad Solahuddin, Ahmad Solahuddin (IJouGS: Indonesian Journal of Gender Studies, 2024)
This study examines Quranic verses, especially Surah Al-Nisa, verse 34, which discusses the relationship between men and women in the household, focusing on the concept of qiwamah. It explores the interpretation of qiwamah using a linguistic approach. The interpretation of qiwamah sees the husband as a protector and provider for his wife, rejecting the idea of male superiority or absolute authority. This article argues that qiwamah is not based on individual competence, but rather, is a permanent responsibility for the husband, supported by the linguistic structure of the Quranic verse. This view contrasts with some Muslim scholars who see qiwamah as dependent on individual ability and not necessarily assigned to the husband. This perspective challenges patriarchal views, suggesting that qiwamah should not justify domestic oppression. Instead, it represents a financial and moral duty for the husband, emphasizing that Islam values women within the household. This interpretation places qiwamah in a broader Quranic context, offering a more comprehensive understanding of gender roles in Islam.